A group decision making model considering both the additive consistency and group consensus of intuitionistic fuzzy preference relations. (November 2016) - Chu, Junfeng; Liu, Xinwang; Wang, Yingming; Chin, Kwai-Sang
Highlights: An approach is proposed to improve the consistency level of IFPR. One algorithm is developed to achieve acceptable level of consensus about IFPRs. A framework is developed for GDM with IFPRs. Abstract: Group decision making with intuitionistic fuzzy preference information involves three steps: the consistency checking process, the consensus checking process and the selection process. In this paper, we investigate the above three steps with respect to additive intuitionistic fuzzy preference relation (IFPR). Firstly, a consistency index is introduced to measure the additive consistency level of IFPR and an automated approach is developed to improve the consistency level with respect to IFPR to an acceptable level. Meanwhile, the group consensus index of IFPR is defined and one algorithm for reaching acceptable level of consensus is developed. Secondly, after implementing this modified algorithm, consistency index and group consensus index are investigated. And we prove that they can hold on, even receive better levels. Thirdly, a framework for group decision making is developed based on IFPR with additive consistency and group consensus. Finally, an illustrative example is presented to demonstrate the effectiveness and applicability of the proposed approach.